2005
DOI: 10.1002/jcb.20623
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of calcium in the differential induction of heat shock protein 70 by heat shock protein 90 inhibitors, geldanamycin and radicicol, in human non-small cell lung cancer H460 cells

Abstract: Both geldanamycin (GA) and radicicol (RA) are HSP90 binding agents that possess antitumour activities. Although the in vitro data indicated that the inhibitory constant of RA is much bigger than that of GA, the in vivo data on drug efficacy might reveal different results. We have recently shown that treatment with GA induces a heat-shock response and that calcium mobilization may be involved in the process. By using induction of HSP70 as the endpoint assay, we found changes in upstream signaling mediators, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Metabolic labeling of nascent proteins was conducted as described [69]. At the end of various treatment periods, the cells were washed with PBS twice, and replaced with RPMI medium containing [ 35 S]methionine (20 μCi/ml) for 2 h. After removal of the medium, the cells were washed with PBS twice and lysed with 2× sample buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic labeling of nascent proteins was conducted as described [69]. At the end of various treatment periods, the cells were washed with PBS twice, and replaced with RPMI medium containing [ 35 S]methionine (20 μCi/ml) for 2 h. After removal of the medium, the cells were washed with PBS twice and lysed with 2× sample buffer.…”
Section: Methodsmentioning
confidence: 99%
“…In mammalian cells, HSR is largely mediated by activation of the transcription factor HSF1. HSF1 normally resides in the cytoplasm in an inactive form bound to hsp90 26. Under conditions of proteotoxic stress, HSF1 becomes activated and translocates to the nucleus where it stimulates expression of a set of heat shock response genes including those encoding inducible chaperones such as hsp70 and hsp27 79.…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, HSF1 undergoes a multi-step process that involves conversion from a monomer to a trimeric nuclear protein complex, followed by binding to the HSEs of the heat-shock genes, thus triggering their transactivation [Pirkkala et al, 2001]. Most recently, we have also demonstrated that treatment of human nonsmall-cell lung cancer H460 cells with GA leads to phosphorylation-activation of HSF1, which in turn stimulates HSP70-1/2 [Shu et al, 2005;Chang et al, 2006a]. In the present study, the results of supershift assays also indicate that HSF1 is the transcription factor that is activated in the GA-induced transactivation of the hsp90 genes in rat 9L cells.…”
Section: Discussionmentioning
confidence: 92%